Pentingnya Komunikasi Dalam Struktur Organisasi - Panji Erlangga; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Communication activities always take place in everyday life, from the moment you open your eyes until you go back to sleep. This means that every activity requires communication, either directly or indirectly, both verbally and nonverbally, including in the context of the organization. Organizations make communication one of the elements of administration, even though the role of communication in the organization is much greater and has many benefits that can be achieved, so it is clear that "communication" activities are very crucial in organizational life. This study uses a qualitative method with a descriptive method to examine the role of communication in the organizational structure. The design of the research activities includes literature studies and observations of communication practices in the organizational setting. The data analysis technique used is qualitative descriptive analysis, namely collecting, reducing, presenting, and drawing conclusions from the data obtained. The data collected is analyzed thematically to determine the patterns, obstacles, and impacts of communication in the organizational structure. Data validation is carried out by triangulating sources and methods to test the validity of the research results. With this method, research is expected to be able to provide a complete picture of the importance of communication in the organizational structure and can offer solutions to communicate more effectively in the organizational environment. Organizational communication can be described as the performance and interpretation of messages between communication units in which the leader is the communicator. Good leaders tend to have good communication skills and therefore will be able to inspire some level of participation from those they lead. They should also be proficient in verbal and non-verbal communication. Effective verbal communication can be achieved through the use of pleasant, polite, and gentle language. Non-verbal communication can be achieved by expressing abstract ideas such as truth, justice, ethics, and religion non-verbally, for example through the use of body language. An organization can develop through communication. Every organization must have a vision, mission, organizational culture, motivation and norms that greatly influence the good or bad of an organization. In reality, communication problems always arise in the organizational process. Communication functions to create an organizational climate that influences the formation of the organizational climate, namely building an organizational culture, namely the values ​​and beliefs that are the focus of the organization. Cultural organizations are part of the internal environment of the organization that cannot be separated because the diversity of cultures that apply in an organization in an amount that is as large as the number of individuals in the organization, its function is as a form of mutual understanding between members of the organization.